Factor Factors Affecting The Mother To Choose Low Interest As Contraception Implant Waterfall Village District In The Field Mmarelan I - MARLIZA, ANANTASIA (Jurnal Martenity and Neonatal, 2013)
The quality of human resource issues can not be separated from the family planning movement efforts to increase awareness and community participation. Implants are the only contraceptive method mengadung progestin with a long service life and in susukkan under the skin.